PEMBUATAN VIDEO PROFIL SEKOLAH PADA SMK YAPIS FAKFAK DALAM RANGKA PROMOSI PENERIMAAN PESERTA DIDIK BARU - Syukron Anas; Al Hamid, Deisya Maulida; Nelson Rumui (Politeknik Negeri Sriwijaya, 2023)
Every institution has a profile as their identity, in the form of writing, pictures, and videos to introduce themselves to the public. The same applies to SMK Yapis Fakfak, one of the vocational education institutions in Fakfak. This profile video is designed with an interesting and informative concept to provide a clear picture of the school, educational programs, facilities, and achievements of SMK Yapis Fakfak. In this profile video, the PkM implementation team collected materials that included pictures and videos of the school, extracurricular activities, teaching and learning atmosphere, as well as interviews with the principal and vice principal. The script of the profile video was carefully crafted to describe the vision, mission and values of SMK YAPIS Fakfak, as well as explain the educational programs provided and their benefits for prospective students. The shooting process was conducted in various locations in the school, highlighting activities of interest and reflecting the diversity of educational programs offered. In the video editing process, relevant scenes were selected and narration was added to explain in more detail about the school excellence of SMK YAPIS Fakfak. The profile video will be uploaded to the school's website, social media channels and video-sharing platforms to ensure its accessibility for prospective students and parents so that it can be an effective promotional medium in supporting enrolment and strengthening the image of SMK YAPIS Fakfak school in the community